[About CEU - Part 2]
Images of students studying in the CEU library. Interview with CEU Library Director Dr. Mária Szlatky who explains that the library was founded by George Soros in 1992 and that its main characteristic is the English language collection. Contains images of the library, the collections and the reading halls. Scenes from a course on gender and from the computer labs.